Analysis of GA Performance on Its Various Parameters for Solving Travelling Salesman NP-Hard Problem - Singh, R.K; Panchal, V.K; Singh, B.K (International Journal of Computer Sciences and Engineering, 2019)
Genetic Algorithm (GA) is a well-known heuristic algorithm inspired by theory of adaptation. GA is applicable to solve many problems of science and engineering. GA performs its operations such as selection, reproduction and mutation to solve a problem. The genetic parameters such as population size, cross over rate and mutation rate control the performance and effectiveness of GA to solve a problem. In this paper, GA is applied to solve Traveling Salesman Problem (TSP). TSP problem is an optimization problem and it is a member of the set NP-Hard problems. In this paper the performance of GA on its parameters is analyzed to solve TSP problem.